KOMUNIKASI KELUARGA JARAK JAUH ANTARA ORANG TUA DAN ANAK DALAM MENJAGA HUBUNGAN KELUARGA DI DESA CAHAYA BARU KECAMATAN MANDAH KABUPATEN INDRAGIRI HILIR - Susilo, Bejo; Susanti, Hevi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Long distance family between parents and children in maintaining family relationships in Cahaya Baru Village. In general, children and their parents have close contact or often communicate face to face because they live in the same house. But other things are similar with parents and children who do not live in the same house or are related long distances. This long distance communication results in unfulfilled needs in the form of emotional relationships that are no longer well established and closeness is reduced resulting in a strained relationship due to lack of communication. This type of research uses qualitative methods with a descriptive approach with the technique of determining research subjects, namely purposive. The author uses data collection techniques through interviews, observation and documentation. The number of informants was 6 people according to the criteria determined purposively. The data analysis technique in this research uses the Miles and Huberman Model and the data validity checking technique, namely triangulation. The research results show that good communication is expected to create the desired communication in long distance relationships between students and their parents. Communication is defined as a form or relationship between two or more people in the process of sending and receiving the right way so that the message in question can be understood. From a communication perspective, the question arises, how does long-distance family communicate with students who come from outside the region